EFFORTS TO IMPROVE SOCIAL SCIENCE (IPS) LEARNING ACHIEVEMENT THROUGH THE STAD LEARNING MODEL FOR GRADE IX A STUDENTS OF UPT SMPN 25 GRESIK ACADEMIC YEAR 2021/2022 - S Tri Wahyuningsih (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The quality of teaching and learning activities is not only observed in terms of results, but also must be surveyed from the process. The quality of the teaching and learning process is characterized by the level of student participation in teaching and learning activities. The level of student participation in teaching and learning activities could always be improved when the teacher attempts to utilize teaching strategies effectively to improve the quality of teaching and learning activities from the aspect of the process. Thus, the quality of the process from the aspect of the results will increase, or it could be mentioned as the improvement of student achievement.Based on the reasons or background of the problems, the author is interested in conducting class action research with the title "Efforts to Improve Social Science (IPS) Learning Achievement through the STAD learning Model for Grade IX A students of UPT SMPN 25 GRESIK Academic Year 2021/2022".    Based on the results of research and discussion, social science learning by applying the learning model student teams achievement division which has been implemented in Class IX A UPT SMPN 25 Gresik can improve student achievement regarding the topic of inter-space dependence and its effects to the welfare of society. This can be seen from the increasing grade point average and classical completeness from cycle I to cycle III. The average score of the class in the first cycle was 67.19 with a classical completion of 62.5 %, the second cycle obtained an average score of 73.13 with a classical completion of 81.25%, and the third cycle obtained an average score of 78.75 with a classical completion of 93.75%.   Student learning activities during the application of student teams achievement division (STAD) learning model also increased. This can be observed from the increase in student activity from cycle I to III. Students who are active in teaching and learning activities in cycle I were 69%, Cycle II were 74% and cycle III were 98 %